Constitutional Law: Nomenklatur Asimetris Atas Negara Bagian Sebagai Subjek Federal di Negara Rusia - Nur Rohim Yunus (ADALAH, 2022)
The naming of states or regions in the Russian Federation is different from other federated states, such as the United States, which uses the word State, or Province in India, Pakistan, and others. Russia has asymmetric subject nomenclature. No homogeneity. The Russian Federation has the Republic, Federally Important Cities, Krais, Oblasts, Autonomous Oblasts, and Autonomous Okrugs. Each Federal Subject has a head, legislature, and constitutional court backed by the constitution and federal law.